PERAN KOMUNIKASI ANTARA PENYULUH DENGAN PEMUDA TANI DALAM PENUMBUHAN MINAT USAHATANI PADI DI DESA KEBONAGUNG KECAMATAN PAKISAJI KABUPATEN MALANG - Piran, Ronaldus Don; Arvianti, Eri Yusnita; Suwasono, Son (Universitas Tribhuwana Tunggadewi, 2017)
The problems of agricultural workforce at this time become one of the main obstacles to advance agriculture. Effective communication between agricultural extension with youth farmer are countermeasures and preventive measures against youth employment reductions and growing interest in food crops, particularly rice. The purpose of this study are to evaluate the role of communication between agricultural extension with the youth farmer and socio-economic condition of youth farmer in the growth of rice farming interest. This research was conducted in the Kebonagung village, Pakisaji District, Malang Regency. The start of this research began in September 2015 and ended in January 2016. The population used is the youth farmer of Kebonagung Village, while the sampel estbalished in purpossive sampling which nembered 31 youth farmers of rice farming. The data analysis used multiple regression analysis and got the regression similarity is Y= 0,691 + 0,370X1 + 0,700X2 + e. The results of multiple regression analysis showed that the value of determination coefficient (Adjusted R²) is 0, 791 which means, 79,1 % of agricultural extension communication role with youth farmer and socio-economic conditions of youth farmer significantly influence the growth of interest in rice farming. Partially, both communication between agricultural extension with youth farmer and socio-economic conditions also significant influence on the growth of rice farming interest. Thus, the youth farmer will be more interested in rice farming if the more effective communication between agricultural extension with youth farmer and socio-economic conditions of youth farmer in creasingly support. Permasalahan tenaga kerja sektor pertanian pada saat ini menjadi salah satu kendala utama memajukan pertanian. Komunikasi yang efektif antara PPL dengan pemuda tani merupakan langkah penanggulangan dan upaya preventif terhadap pengurangan tenaga kerja muda dan penumbuhan minat di subsektor tanaman pangan, khususnya tanaman padi. Tujuan penelitian ini adalah mengevaluasi peran komunikasi antara penyuluh pertanian dengan pemuda tani dan kondisi sosial ekonomi pemuda tani dalam penumbuhan minat usahatani padi. Penelitian ini dilaksanakan di Desa Kebonagung Kecamatan Pakisaji Kabupaten Malang. Awal penelitian dimulai pada bulan September 2015 dan berakhir pada bulan Januari 2016. Populasi yang digunakan adalah pemuda tani Desa Kebonagung, sedangkan sampel ditentukan secara purpossive sampling dengan jumlah 31 pemuda tani yang bertani padi. Analisis data menggunakan analisis regresi berganda dan diperoleh persamaan regresi Y= 0,691 + 0,370X1 + 0,700X2 + e. Hasil analisis regresi menunjukkan bahwa nilai koefisien determinasi (Adjusted R²) adalah 0,791 yang berarti, 79,1 % peran komunikasi penyuluh dengan pemuda tani beserta kondisi sosial ekonomi pertanian berpengaruh signifikan terhadap penumbuhan minat usahatani padi. Secara parsial baik komunikasi antara penyuluh dengan pemuda tani maupun kondisi sosial ekonomi juga berpengaruh signifikan terhadap penumbuhan minat usahatani padi. Dengan demikian, pemuda tani akan semakin berminat pada usahatani padi apabila semakin efektif komunikasi antara penyuluh dengan pemuda tani dan kondisi sosial ekonomi pemuda tani semakin menunjang.